2011
DOI: 10.1080/14742837.2011.614108
|View full text |Cite
|
Sign up to set email alerts
|

Framed Encounters with Conservation and Mining Development: Indigenous Peoples' use of Strategic Framing in Suriname

Abstract: While studies on the use of framing as a strategy for social movements have proliferated in the past 20 years, little is still known about how and why the frames vary across social movement actors and/or events. This article addresses this knowledge lacuna by comparing and contrasting Indigenous peoples' use of rights and identity frames in response to conservation and development events in Suriname. The variation in frames, and possible reasons for these variations, was compared across actors and events by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…They perceive contamination as a threat to the place and people that they value, and respond by organizing to fight for their established way of life (Wulfhorst 2000). In her study of conservation and mining development plans in Suriname, Haalboom (2011) found that indigenous people protested their exclusion from decision making by highlighting their history of connection to the geographic area, and by arguing that their community as a collective was inseparable from the land.…”
Section: Culture Identity and Environmental Hazardsmentioning
confidence: 99%
“…They perceive contamination as a threat to the place and people that they value, and respond by organizing to fight for their established way of life (Wulfhorst 2000). In her study of conservation and mining development plans in Suriname, Haalboom (2011) found that indigenous people protested their exclusion from decision making by highlighting their history of connection to the geographic area, and by arguing that their community as a collective was inseparable from the land.…”
Section: Culture Identity and Environmental Hazardsmentioning
confidence: 99%
“…Furthermore, few researchers examine frames of specific street demonstrations or protest events (see Gerhards and Rucht 1992 for an exception). Most scholars scrutinize frames of a whole movement, analyzing newspaper articles, texts, or documents communicated by organizations over a longer period of time (e.g., Ferree 2003;Haalboom 2011;Noonan 1995). Accordingly, frames are usually operationalized in a broad sense.…”
mentioning
confidence: 99%
“…To analyze how social movements develop and circulate meanings, many researchers draw upon theories of frames and framing (Snow & Benford, 1992;Gamson, 1995;Haalboom, 2011;Mendes, 2011;Haydu, 2012;Heidemann, 2012). Frames are understood as schemata used by actors both to interpret the world and to define what can and should be done in the world.…”
Section: Discursive Practice and Collective Identitymentioning
confidence: 99%